The Effects of Pancreatic Microcirculatory Disturbances on Histopathologic Tissue Damage and the Outcome in Severe Acute Pancreatitis. Issue 2 (February 2016) - Tomkötter, Lena; Erbes, Johannes; Trepte, Constantin; Hinsch, Andrea; Dupree, Anna; Bockhorn, Maximilian; Mann, Oliver; Izbicki, Jakob R.; Bachmann, Kai
Abstract : Objectives: Severe acute pancreatitis is an inflammatory disease of the pancreas with a high morbidity and mortality. To date, no causal treatment is known. The aim of the present study was to analyze the impact of pancreatic microcirculatory disturbances in severe acute pancreatitis and to correlate the effects with histopathologic tissue damage and outcome. Methods: Severe acute pancreatitis was induced in 129 pigs by injection of glycodeoxycholic acid into the pancreatic duct. Pancreatic microcirculation, pancreatic tissue oxygenation, histopathologic tissue damage, and survival were measured and analyzed. Results: Our study demonstrates a strong correlation between pancreatic microcirculatory disturbances and histopathologic tissue damage ( r = 0.728; P < 0.001). Furthermore, we showed a strong correlation between tissue oxygenation and the severity of the pancreatitis according to an established porcine pancreatitis score ( r = 0.694; P < 0.001). In addition, disturbances of the pancreatic microcirculation were shown to be associated with an increased mortality rate in severe acute pancreatitis. Conclusions: We found that pancreatic microcirculatory disturbances have significant effects on histopathologic tissue damage and the outcome of severe acute pancreatitis. For a better survival of severe acute pancreatitis, the treatment should focus on an improvement of pancreatic microcirculation.